If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(2m + 1) = 0 Reorder the terms: 8(1 + 2m) = 0 (1 * 8 + 2m * 8) = 0 (8 + 16m) = 0 Solving 8 + 16m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 16m = 0 + -8 Combine like terms: 8 + -8 = 0 0 + 16m = 0 + -8 16m = 0 + -8 Combine like terms: 0 + -8 = -8 16m = -8 Divide each side by '16'. m = -0.5 Simplifying m = -0.5
| -9-8=10x+10-9x | | x+0.25=-1.25 | | 3(-2.5y+7)=-36 | | -2(4-x)-7=15 | | 12(p+5)=13p+2 | | 44=5x-3x | | 3(y-5)=-3y | | 8x-5-2x+5=x-18+8x | | 2x+15=95 | | 22+3x=-4(5-6x) | | 32=4 | | 10p-45=3(p-15) | | -3(a+5)+9=15 | | 1-6n+n=9 | | 45+-.5y+3(45-.5Y)+2Y=180 | | 5x+28=20x | | 293.92=17.6h | | 25=5 | | x^2+y^2+4y-12=0 | | s=56s=t÷6 | | 14d-21=6d+3 | | 4(h-5g)= | | 5m+3n=14 | | 6v^2-7v+2=0 | | 2-18y^2=0 | | 3x-2y=-36 | | 2x-3x=-3-8 | | ab-6c=5 | | 5+3(q-4)=2(q-4) | | 2(5a-13)=47 | | x-16=21 | | (9t+5)+(3t-6)= |